Differences in Clinical Outcomes of Adults Referred to a Homeless Transitional Care Program Based on Multimorbid Health Profiles: A Latent Class Analysis - Smith, Colin M.; Feigal, Jacob; Sloane, Richard; Biederman, Donna J. (Frontiers in Psychiatry, 2021)
Background: People experiencing homelessness face significant medical and psychiatric illness, yet few studies have characterized the effects of multimorbidity within this population. This study aimed to delineate unique groups of individuals based on medical, psychiatric, and substance use disorder profiles, and compare clinical outcomes across groups. Methods: We extracted administrative data from a health system electronic health record for adults referred to the Durham Homeless Care Transitions program from July 2016 to June 2020. We used latent class analysis to estimate classes in this cohort based on medical, psychiatric and substance use disorder diagnoses and compared health care utilization, overdose, and mortality at 12 months after referral. Results: We included 497 patients in the study and found 5 distinct groups: “low morbidity” (referent), “high comorbidity,” “high tri-morbidity,” “high alcohol use,” and “high medical illness.” All groups had greater number of admissions, longer mean duration of admissions, and more ED visits in the 12 months after referral compared to the “low morbidity” group. The “high medical illness” group had greater mortality 12 months after referral compared to the “low morbidity” group (OR, 2.53, 1.03-6.16; 95% CI, 1.03-6.16; p = .04). The “high comorbidity” group (OR, 5.23; 95% CI, 1.57-17.39; p < .007) and “high tri-morbidity” group (OR, 4.20; 95% CI, 1.26-14.01; p < .02) had greater 12-month drug overdose risk after referral compared to the referent group. Conclusions: Distinct groups of people experiencing homelessness are affected differently by comorbidities. Health care programs for this population should address their risk factors accordingly.